2019
DOI: 10.3390/f10030244
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Responses in Litterfall and Litter Decomposition in Red Pine (Pinus densiflora S. et Z.) Stands Disturbed by Pine Wilt Disease

Abstract: Research Highlight: Forest disturbance by insects or disease can have a significant influence on nutrient return by litterfall and decomposition, but information regarding disturbance gradients is scarce. This study demonstrated that the disturbance intensity caused by pine wilt disease greatly altered the quality and quantity of carbon (C) and nitrogen (N) in litterfall components and decomposition processes. Background and Objectives: This study was conducted to evaluate the C and N status of litterfall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The C concentrations of the litterfall components were similar to other study results, in which the leaf litter was approximately 50% in P. densiflora stands in South Korea (Kim et al 2019) and 47.5% in Q. variabilis stands in China (Du et al 2017), but lower than those of P. brutia stands (51.24 %) in Turkey (Erkan et al 2020). The mean N concentrations of the leaf, branch, reproductive, and miscellaneous litter in this study are comparable to other studies in Q. variabilis in China (Du et al 2017) and in P. brutia stands in Turkey (Erkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The C concentrations of the litterfall components were similar to other study results, in which the leaf litter was approximately 50% in P. densiflora stands in South Korea (Kim et al 2019) and 47.5% in Q. variabilis stands in China (Du et al 2017), but lower than those of P. brutia stands (51.24 %) in Turkey (Erkan et al 2020). The mean N concentrations of the leaf, branch, reproductive, and miscellaneous litter in this study are comparable to other studies in Q. variabilis in China (Du et al 2017) and in P. brutia stands in Turkey (Erkan et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…C and N concentrations of litterfall components. The variations in the C and N concentrations of the litterfall components are mainly determined by the species and sampling months (Thomas, Martin 2012;Kim et al 2019;See et al 2019;Erkan et al 2020). Many studies have reported that the C concentration of the litterfall is negatively correlated with the N and positively correlated with the lignin concentration (Macinnis-Ng, Schwendenmann 2015; Kim et al 2017;See et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few studies on litter decomposition have been conducted in pine forests, there is limited information on the effects of physicochemical litter quality on decomposition of different pine litter species, because these studies contain only a simple description of changes in nutrient elements in decaying litter [38][39][40][41]. Moreover, it is difficult to directly compare the results of these studies, because each pine species was independently studied at different times, with varying areas, litter type, and forest floor characteristics [38][39][40][41][42][43][44][45][46]. Also, it is not clear if the differences in decomposition rate of each type of pine litter is attributable to the kinds of environmental conditions present or the chemical properties of the litter.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other analytical techniques, pyrolysis-gas chromatography/mass spectrometry (py-GC/MS) is more efficient and can provide a larger view of SOM chemical structural information [19,22]. In addition, py-GC/MS also facilitates a better understanding of the extent of the decomposition/preservation in SOM pools and a detailed comparison of the SOM produced under different managements [23][24][25]. Furthermore, advantages of this pyrolysis analysis over others include good repeatability and a relatively small amount of soil samples required [26][27][28].…”
mentioning
confidence: 99%